Methodology for the formation of professional knowledge of future teachers of fine arts through spatial learning - visual 3D images - Yadgarov , Nodir (Рroblems of engineering and professional education, 2024)
The article considers the professional skill of the future drawing teacher - this is an integrative feature that describes his readiness to work with visual images in the space of his work. Drawing describes the teacher's practical readiness to perform his work with spatial-visual representations of details and structures based on his knowledge and compensation. In the process of forming the professional skills of the future drawing teacher in higher educational institutions, their qualitative components, that is, spatial- visual 3D images, are interconnected with each other and with the engineering elements of the structural system. In determining the meaning of the concept of "spatial-visual 3D images" an important role is played by the assessment of the indicators of the development of spatial imagination. It determines the following indicators of spatial imagination development: stability, width, flexibility, depth, completeness, dynamic state of geometric images, appropriateness, as well as types of work with spatial imagination in solving problems. The set of these indicators, in our opinion, describes the formation of spatial images in students as fully and comprehensively as possible. The study allowed us to determine the spatial-visual 3D image competence, which describes the level of preparation of teachers for professional activities, as a necessary part of professional skills.